Role of echocardiography in screening for portopulmonary hypertension in liver transplant candidates: a meta-analysis - Yin, Xin (PeerJ, 2020)
OBJECTIVES: To demonstrate the screening value of echocardiography for portopulmonary hypertension (POPH) in liver transplant candidates. DESIGN: Systematic review and meta-analysis. BACKGROUND: POPH is a complication of end-stage liver disease that adversely affects the outcome of orthotopic liver transplant. There are no specific symptoms in the early stage of POPH. POPH reduce the survival rate of patients with end-stage liver disease specially if they are not diagnosed. Therefore, early detection may improve prognosis. The objective of this study is to explore the screening value of echocardiography on liver transplant candidates for screening of POPH compared to right heart catheterization (RHC). METHOD: PubMed, EMBASE and the Cochrane Library were searched by two independent reviewers for potentially eligible studies published up to 30 June 2019 to retrieve data based on per-patient analysis. STATA, Meta-DiSc, and RevMan were applied to perform this meta-analysis. RESULTS: Our search yielded 1576 studies, of which 11 satisfied the inclusion criteria. The pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR) and area under the summary receiver operating characteristic (SROC) curve (AUC) of echocardiography for POPH were 0.85 (95% CI [0.65–0.94]), 0.83 (95% CI [0.73–0.90]), 4.99 (95% CI [3.03–8.21]), 0.19 (95% CI [0.07–0.46]), and 0.91 (95% CI [0.88–0.93]), respectively. Deeks’ funnel plot did not indicate the existence of publication bias (P = 0.66). CONCLUSIONS: Echocardiography, a noninvasive modality, provides superior screening for POPH, but the diagnosis of POPH still requires RHC. PROSPERO registration number CRD42019144589.